Case Report: Novel Biallelic Variants in the COL18A1 Gene in a Chinese Family With Knobloch Syndrome - Chong, Shuk Ching; Yuen, Yuet-Ping; Cao, Ye; Fan, Sze-Shing; Leung, Tak Yeung; Chan, Emily K. Y.; Zhu, Xian Lun (Frontiers in Neurology, 2022)
Knobloch syndrome is a rare collagenopathy characterized by severe early onset myopia, retinal detachment, and occipital encephalocele with various additional manifestations due to biallelic changes in the COL18A1 gene. Here we reported a Chinese family with two affected siblings presented with antenatal occipital encephalocele, infantile onset retinal detachment and pronounced high myopia at early childhood. Quartet whole exome sequencing was performed in this family and identified both siblings carried novel compound heterozygous variants in the COL18A1 gene (NM_001379500.1) : the maternally inherited variant c.1222-1G>A at the consensus acceptor splice site of intron 8, and the paternally inherited frameshift variant c.3931_3932delinsT p.(Gly1311Serfs*25) in the last exon. Both patients had successful surgical treatment for the occipital encephalocele soon after birth. They had normal neurocognitive outcome and good general conditions examined at age of 7 years old for the elder sister and 4 years old for the younger brother. The younger brother developed infantile onset retinal detachment at 7 months of age while the sister had high myopia without signs of retinal detachment till 7 years old. This report expands the phenotype and genotype spectrum of Knobloch syndrome with antenatal and postnatal findings.